Current context and the experience of Brazilian Medical Societies with Specialist Title Exams - GERSON ALVES PEREIRA JÚNIOR; RAMIRO COLLEONI NETO; JAIR GIAMPANI JÚNIOR; JORGE CARVALHO GUEDE; ANA CRISTINA KFOURI CAMARGO; FÁBIO TERUO MATSUNAGA; ROSELI MIEKO YAMAMOTO NOMURA; FELIPE OLIVEIRA MARQUES; JOSÉ EDUARDO LUTAIF; CESAR EDUARDO FERNANDES (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT The editorial discusses the need for the Specialist Title to be valued by Medical Societies, as a stage after the conclusion of medical residency and a mandatory prerequisite for taking the tests. Finally, it shows the experience of seven Medical Societies with their specialist title exams.